A Novel Method of Semantic Relatedness Measurements for Word Sense Disambiguation on English AlQuran - Abdul-Ameer Mussa, Sarah; Tiun, Sabrina (Bulletin of Electrical Engineering and Informatics, 2015)
The methods and background introduced in this article concern on the interpretation of the Quranic text in English translation using word sense disambiguation. Three measures of semantic similarity measures: Wu-palmer, Lin and Jiang-Conrath, and their combinationÂ  were used to identify words sense on the English Quranic text, in which comparison and detailed evaluation was carried out.Â  The finding results showed that the WuâPalmer approach determine the similarity of senses asÂ  the most accurate, followed by the Lin, and JiangâConrath.Â  However, the combination of these measurements (novel method) achieves higher accuracy in comparison with the individual result of each measure before.